Heterozygous Triplication of Upstream Regulatory Sequences Leads to Dysregulation of Matrix Metalloproteinase 19 in Patients with Cavitary Optic Disc Anomaly. Issue 3 (13th March 2015) - Hazlewood, Ralph J.; Roos, Benjamin R.; Solivan‐Timpe, Frances; Honkanen, Robert A.; Jampol, Lee M.; Gieser, Stephen C.; Meyer, Kacie J.; Mullins, Robert F.; Kuehn, Markus H.; Scheetz, Todd E.; Kwon, Young H.; Alward, Wallace L.M.; et al.
Abstract : Cavitary optic disc anomaly (CODA) is a congenital malformation of the optic nerve that has similarities with the damage to the optic nerve seen in glaucoma. Our studies of an autosomal dominant pedigree with CODA identified a mutation that regulates expression of the matrix metalloproteinase 19 ( MMP19 ) gene, which is strongly expressed in the optic nerve. Dysregulation of MMP19 is a plausible cause of CODA and may have more general roles in the pathophysiology of glaucoma and other optic nerve diseases. ABSTRACT: Patients with a congenital optic nerve disease, cavitary optic disc anomaly (CODA), are born with profound excavation of the optic nerve resembling glaucoma. We previously mapped the gene that causes autosomal‐dominant CODA in a large pedigree to a chromosome 12q locus. Using comparative genomic hybridization and quantitative PCR analysis of this pedigree, we report identifying a 6‐Kbp heterozygous triplication upstream of the matrix metalloproteinase 19 ( MMP19 ) gene, present in all 17 affected family members and no normal members. Moreover, the triplication was not detected in 78 control subjects or in the Database of Genomic Variants. We further detected the same 6‐Kbp triplication in one of 24 unrelated CODA patients and in none of 172 glaucoma patients. Analysis with a Luciferase assay showed that the 6‐Kbp sequence has transcription enhancer activity. A 773‐bp fragment of the 6‐Kbp DNA segment increased downstream gene expression eightfold, suggesting that triplication of this sequence may lead to dysregulation of the downstream gene, MMP19, in CODA patients. Lastly, immunohistochemical analysis of human donor eyes revealed strong expression of MMP19 in optic nerve head. These data strongly suggest that triplication of an enhancer may lead to overexpression of MMP19 in the optic nerve that causes CODA.